2022
DOI: 10.21873/invivo.13010
|View full text |Cite
|
Sign up to set email alerts
|

Study of Therapeutic Effects of Losartan for Sarcopenia Based on the F344xBN Rat Aging Model

Abstract: Background/Aim: Sarcopenia is an age-related disease in which muscle mass and strength are markedly reduced. There are few effective treatments, but the angiotensin II receptor antagonist losartan has been reported to be effective. Our aim was to evaluate the therapeutic effectiveness of losartan for sarcopenia and explore the underlying mechanisms. Materials and Methods: We investigated body weight, muscle mass (gastrocnemius, soleus, peroneus longus, and tibialis anterior muscles), and serum markers in an ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Kang et al tested the effect of losartan in a rat model of sarcopenia. Male 4-week-old F344xBN rats were administered 0.6 g/L losartan diluted in drinking water over a period of 18 months [166]. Average muscle mass of the tibialis anterior (TA), soleus, and peroneus longus muscles was increased by losartan treatment combined with an exercise program, compared to exercise alone [166].…”
Section: Drug Repositioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Kang et al tested the effect of losartan in a rat model of sarcopenia. Male 4-week-old F344xBN rats were administered 0.6 g/L losartan diluted in drinking water over a period of 18 months [166]. Average muscle mass of the tibialis anterior (TA), soleus, and peroneus longus muscles was increased by losartan treatment combined with an exercise program, compared to exercise alone [166].…”
Section: Drug Repositioningmentioning
confidence: 99%
“…Male 4-week-old F344xBN rats were administered 0.6 g/L losartan diluted in drinking water over a period of 18 months [166]. Average muscle mass of the tibialis anterior (TA), soleus, and peroneus longus muscles was increased by losartan treatment combined with an exercise program, compared to exercise alone [166]. Interestingly, soleus (slow twitch type I) and peroneus longus (fast twitch type II) muscle mass was also increased without the need for an exercise program.…”
Section: Drug Repositioningmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study involving 740 older adults revealed a significant positive correlation between calcium intake and appendicular lean mass (ALM) [ 134 ]. Animal studies have also suggested that losartan may slow down muscle degeneration, promote clinical benefits, and provide protection for patients with sarcopenia [ 135 , 136 ].…”
Section: Introductionmentioning
confidence: 99%